2000
DOI: 10.1053/jlts.2000.19058
|View full text |Cite
|
Sign up to set email alerts
|

Posttransplantation prevention and treatment of recurrent hepatitis B

Abstract: Key PointsProphylaxis of Recurrent Hepatitis B 1. Although standard prophylaxis with antibody to hepatitis B surface antigen immunoglobulins (HBIG) is effective, it is difficult to administer and must be administered indefinitely. 2. Preemptive therapy with lamivudine reduces the early risk for recurrence after transplantation, but maintenance with either famciclovir or lamivudine has been ineffective in sustaining remission. R ecurrence of hepatitis B virus (HBV) infection in the liver graft remains a major i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Other studies identified the protective role played by HDV in prevention of HBV recurrence after LT, because HDV exerts a suppressive effect on HBV replication after LT. Regarding HBVrelated ALF, the second group at lower risk of HBV recurrence, some authors asserted that the acute and massive necrosis secondary to fulminant infection can led to a natural clearance of the viral load [82,83].…”
Section: Recurrence Of Hbv Infection After Ltmentioning
confidence: 99%
“…Other studies identified the protective role played by HDV in prevention of HBV recurrence after LT, because HDV exerts a suppressive effect on HBV replication after LT. Regarding HBVrelated ALF, the second group at lower risk of HBV recurrence, some authors asserted that the acute and massive necrosis secondary to fulminant infection can led to a natural clearance of the viral load [82,83].…”
Section: Recurrence Of Hbv Infection After Ltmentioning
confidence: 99%
“…Viral eradication is rare with any currently approved medication, including interferon, foscarnet, ganciclovir, famciclovir, and lamivudine. 40,[69][70][71][72][73][74] Lamivudine is by far the most effective agent to reduce HBV DNA levels. Perrillo et al 40 reported on 52 patients, all with recurrent HBV after OLT and 60% of whom had undetectable HBV DNA at the end of treatment, with HBeAg seroconversion in 31% and a YMDD mutation rate of 27% in the cohort.…”
Section: Treatment Of Recurrent or De Novo Hepatitis B In Liver Transmentioning
confidence: 99%
“…20 Because the YMDD mutant replicates inefficiently compared with wild-type HBV, the relatively small number of virions may be unlikely to escape HBIG binding. The use of combination lamivudine and HBIG (high or low dose) has been reported in more than 135 patients treated worldwide, 21 with recurrence rates consistently less than 10%. In a study from the University of California at Los Angeles, 22 13 patients were treated prophylactically with lamivudine and high-dose HBIG (starting with 10,000 IU during the anhepatic phase).…”
Section: Preemptive Treatment With Nucleoside Analogues Alone or In Cmentioning
confidence: 99%